2008
DOI: 10.2353/ajpath.2008.070629
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia-Related Inflammatory Cytokines Regulate Interleukin-6 Expression in Human Decidual Cells

Abstract: Preeclampsia, a common pregnancy disorder associated with an increase in systemic inflammation, is the leading cause of maternal and fetal morbidity and mortality throughout the world. It is associated with shallow extravillous trophoblast invasion of the decidua, leading to uteroplacental blood flow that is inadequate for the developing fetal-placental unit. In preeclamptic women, interleukin-6 (IL-6) levels in plasma, but not placenta, are elevated, prompting evaluation of the decidua as a potential source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 59 publications
6
103
0
6
Order By: Relevance
“…Levels of IL-6 in the amniotic fluid of women with infection were found to enhance the production of uterine contraction-mediating prostaglandin E 2 when incubated with amnion or DCs, thereby suggesting a mechanism to account for CAM-associated PTD. 27 As in our evaluation of preeclamptic versus control decidual specimens, 10 the current study observed IL-6 immunostaining localized primarily in the cytoplasm of DCs that increased significantly in CAM versus control placental sections (HSCOREs, P Ͻ 0.05). In contrast, IL-6 HSCOREs were significantly lower in adjacent interstitial trophoblasts where the staining is primarily perimembranous and similar between patients and control subjects.…”
Section: Discussionmentioning
confidence: 79%
“…Levels of IL-6 in the amniotic fluid of women with infection were found to enhance the production of uterine contraction-mediating prostaglandin E 2 when incubated with amnion or DCs, thereby suggesting a mechanism to account for CAM-associated PTD. 27 As in our evaluation of preeclamptic versus control decidual specimens, 10 the current study observed IL-6 immunostaining localized primarily in the cytoplasm of DCs that increased significantly in CAM versus control placental sections (HSCOREs, P Ͻ 0.05). In contrast, IL-6 HSCOREs were significantly lower in adjacent interstitial trophoblasts where the staining is primarily perimembranous and similar between patients and control subjects.…”
Section: Discussionmentioning
confidence: 79%
“…Much attention has been paid to the secretion of the proinflammatory cytokines described above as well as chemokines and VEGF by decidual NK cells and their possible roles in implantation that involves invasion of EVT into the decidua and in vascular remodeling of the uterine spiral arteries that insures an adequate blood supply to the developing fetus (14, 18-21,). IL-6 has received particular attention because of its possible role in preeclampsia (33). However, decidual macrophages that may make equal or more extensive contributions to these and other pregnancy-related phenomenon have been little studied.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 6 Decidual cells from preeclamptic patients exhibit high IL6 production (Lockwood et al, 2008).…”
Section: Il6mentioning
confidence: 99%